BUSINESS BEHAVIOR AND BUSINESS PERFORMANCE OF BATIK ENTREPRENEURS DURING THE COVID PANDEMIC 19 - Tona Lubis; Firmansyah Firmansyah (Journal of Business Studies and Management Review, 2021)
The emergence of the Covid-19 pandemic has caused huge losses throughout the world. The main victims of this pandemic are micro, small & medium enterprises (SMEs), including Batik SMEs Industry. During the Covid-19 pandemic, it becomes the basis that there will be fundamental changes in business behavior and performance. In general, the ultimate goal of this research is to model the impact of the Covid 19 Pandemic on business behavior and business performance of Jambi Batik entrepreneurs. This study used qualitative research methods with phenomenological type. This qualitative research analysis will be assisted by using the Nvivo software. Based on research, it can be concluded that the downturn of these business entrepreneurs can be seen from their business behavior and business performance. In terms of business behavior, it can be seen that the batik business in Jambi province is experiencing downturn due to 3 reasons. These are Efficiency, Innovative and Creative, while in business performance, the downturn of batik business entrepreneurs in Jambi Province can be seen from 2 reasons, these are reduced profits and decreased sales turnover.